Agenda Meeting of Floor Managers and Floor Leaders (1976)
This document is the July 13, 1976 agenda for a meeting of Floor Managers and Floor Leaders at the Democratic National Convention. It addresses organizational issues, including matching whips with delegates and improving communication among whips, leaders, managers, and campaign trailers. The group's goals include circulating nomination petitions, completing a delegate count on candidate leanings, and reporting results by designated deadlines. Plans are outlined for a Wednesday demonstration supporting Brown, as well as promoting a $10 fundraiser for the United Farm Workers featuring the Governor and Cesar. The agenda also emphasizes rumor control, coordinated information sharing, attention to California's organization, and scheduling a follow-up meeting.